Africa Climate Conference 2013: Addressing Priority Research Gaps to Inform Adaptation Decision-Making in Africa, Frontiers in African Climate Science Research and Applications - Afiesimama, Ernest; Anyah, Richard; Asrar, Ghassem; Awulachew, Seleshi Bekele; Diallo, Adama A; Garanganga, Brad; Graham, Richard; Hewitson, Bruce; Kane, Cheikh; Lamb, Pete; Lucio, Filipe; Mason, Simon J.; et al. (2013)
The Africa Climate Conference 2013, due to be held October 15-18, 2013 in Arusha (Tanzania), aims to narrow the communications gap currently existing between African decision-makers and climate scientists and to develop a coordinated collaborative research strategy to enhance climate science outputs so that they may better inform climate early warning responses and adaptation in Africa. This document outlines, in the context of global climate initiatives, the key research frontiers for African climate that will be addressed. In a departure from usual practice, motivated by the imperative of ‘mainstreaming use of climate information in decision making’, research priorities are ordered according to their alignment with emerging priority needs for African users. As part of its activities the conference will review and validate these ‘frontier’ research priorities (see also the conference concept note).